DAMPAK COVID-19 TERHADAP PENDAPATAN PEDAGANG (STUDI KASUS DI PASAR PETERONGAN JOMBANG) - Sa’adah, Lailatus; Umam, Khothibul (Economicus, 2021)
The formulation of the problem what is the impact felt by traders, especially the income of traders during the covid 19 outbreak This study aims to find out how the impact of covid 19 on the income of traders before the occurrence of covid 19, during the covid 19 pandemic and in the new normal, at the same time providing benefits for the government and traders so that they can solve a similar problem if it occurs in the future. The type used in this study is qualitative, the information collection techniques used are observation and interviews. The research population which is also the research sample is the traders of the Jombang Peterongan market, with the determination of the sample that the sample obtained is 100 respondents. And qualitative descriptive information analysis techniques using the Miles and Huberman model. The results of this study indicate that the income of Peterongan traditional market traders is sufficiently increased and stable so that they can meet their daily needs and support the traders 'economy and traders' income is also influenced by several factors, including the increasing number of regular customers and also the more crowded consumers who shop at the Peterongan market. . The Covid 19 pandemic has a very serious impact, the income of Peterongan Jombang traditional market traders has decreased very drastically, reaching 70% -80% experienced by traders and causing market closures. There was an increase in income in the normal era experienced by traders reaching 40% compared to the Covid 19 pandemic.